CONCEPTUAL FRAMEWORK FOR TRAINING FUTURE TEACHERS BASED ON DOMINANT COGNITIVE STYLES (EDUCATION IN THE 21ST CENTURY, 2023)
The article considers the main conceptual foundations of training future teachers based on dominant cognitive styles. The relevance of high-quality training of pedagogical personnel in accordance with changing needs and opportunities for social reality for the state and society as a whole is justified. The author addresses the question of the need to use the potential of individual characteristics of students – cognitive styles. Various interpretations of the concept of "cognitive style" from the point of view of various scientific fields, copyright approaches are considered. The main features of formation and manifestations of cognitive style in a person are described. The problem of taking into account only 1-2 diads of cognitive styles in the training process. At the same time, other styles are underestimated, and it is not realistic to take into account all known cognitive styles. They do not provide for the possibility of future teachers having a mixed style. In addition, there is a difficulty in the use of material by non-specialists in the field of psychology. These provisions indicate the rationality of accounting for cognitive metastyle "differential-integrality" in students. The article gives an essential characteristic of metastyle. The author points out that tasks should be both on the development of a dominant and subordinate cognitive style. Offers a description of possible job options for students with one or another dominant cognitive style. It is noted that this training organization avoids the problem of cognitive dissonance. Interacting in heterogeneous groups, future teachers learn the ability to organize productive joint activities, establish communication with representatives of different styles. The article discusses the rationality of a learning goal based on cognitive styles, and offers guidelines for its implementation. Its versatile action in didactic, psychological and social aspects is described.
Keywords: Keywords: future teachers, cognitive styles,